Intralesional injection of fotolon for photodynamic therapy of basal cell carcinoma - T. E. Sukhova (Biomedical Photonics)
The new method of photodynamic therapy for basal cell skin carcinoma with intralesional injection of photolon (at dose of 1.44-2.50 mg/cm3 of tumor volume 15 min before irradiation) was developed in the department of dermatology, venerology and dermatooncology in The State Budgetary Healthcare Institution of Moscow Area Moscows regional research clinical institute n.a. M.F. Vladimirskiy. The efficacy of the developed method was evaluated in clinical studies in 30 patients comparing with the group of 32 patients who had conventional PDT with typical intravenous injection of photolon (at dose of 2.0–2.5 mg/kg of body weight 3 h before irradiation). The characteristics of irradiation were the same both in the study and in the control groups: power density of 0.31-0.47 W/cm2, light dose of 300 J/cm2. Compared PDT regimens had similar efficiency. As a result of the performed treatment complete tumor regression was achieved in 93.3% patients with intralesional injection of photolon and in 90.6% patients with intravenous injection. The rate of patients with 2-year recurrence-free survival after intralesional injection of photolon accounted for 96.7%; after intravenous injection – 93.8%. However, the developed method demonstrated superior safety comparing with intravenous injection of photolon: such as there was no need for light regimen after intralesional injection of photolon, there were no cases of skin phototoxicity (12.5% for intravenous injection), no increasing of transaminases (37.5% for intravenous injection).